Strain-rate sensitivity of unstable localized phase transformation phenomenon in shape memory alloys using a non-local model. (15th June 2015) - Ahmadian, Hossein; Hatefi Ardakani, Saeed; Mohammadi, Soheil
Highlights: A new softening function is proposed in a fully thermodynamically consistent framework for SMA materials. An integral-type nonlocal model is adopted to deal with mesh dependency phenomenon. The coupled equations are discretized using a finite element procedure. Thorough investigation of the interacting effects of size, geometry and strain rate on SMA material behavior. Abstract: In this work, the original local model of Boyd and Lagoudas (1996) has been extended by proposing a new softening function to examine the localized macro behavior resulted from unstable phase transformation phenomenon in thin sheets of shape memory alloys (SMAs). In addition, an integral type non-local softening model is adopted to overcome the mesh dependency problem of local softening models. Due to strong thermo-mechanical coupling in SMAs, a staggered scheme has been used to take into account the coupling effects on material behavior. Inclusion of such effects has revealed that instability induced by unstable phase transformation could be surmounted by increasing the strain rate. The simulations have been verified against the available experimental and numerical data, showing a good agreement.